The Review of Act Number 39 year 2004 Concerning The Placement and Protection for Indonesian Workers Abroad - Lalu Husni; Idrus Abdullah; RR Cahyowati (Unram Law Review, 2017)
Labor migration in the era of free trade is a necessity, as part of the international community, Indonesia must participate in the globalization era, so it can not withstand nationals to seek a better life abroad. The purpose of this study to know and understand the weaknesses of the Act No. 39 of 2004 on the placement and protection of migrant workers, knowing and understanding the formulation of norms of protection of migrant workers to protect it properly. Research methods, normative law research, with the statute approach, conceptual approach, and conceptual approach. The types and sources of legal materials, using primary legal resourse, legal resourse secondary, and tertiary legal resource. Mechanical collection of legal materials, is done by performing a search, collection and documentation, processing and analysis of legal materials through a process of legal reasoning logical, systematic and coherent. Conclusion, weakness No..39 Act of 2004 regarding the Placement and Protection of Migrant Workers so it can not protect properly, this is due to provisions that prohibit or liability, but is not followed by the threat of legal sanction. Their norms do not provide clear who is the subject of law. Their formulation of norms "skill" that should be in the form of "necessity", so that the selection of a local recruit migrant workers can actually be done properly, and can prevent ekploitation human / human trafficking. The existence of norms regulating the legal subjects that are outside the boundaries of the Unitary Republic of Indonesia. Provisions that contradict each other (inconsistency). There are provisions governing unilateral legal subjects. Legal uncertainty because the agreements made on the basis of agreement between the workers / laborers (prospective TKI) with the employer / user services, the formulation of norms of protection of migrant workers to protect properly, namely by stating the principles of humanitarianism and the principle of national responsibility as the foundation footing.